The Impact of Hedonic Buying Motivation, Shopping Way of Life, Positive Emotion, and Variety of Selection on Impulse Searching for in Tokopedia Online Shop - Angga Putri Ekanova; Anisah Anisah; Lies Handrijaningsih; Septi Mariani T.R (Ilomata International Journal of Social Science, 2022)
The advancement of communication and information technology is increasing rapidly. Utilization of the Internet is an inseparable part of people's lives, so that many companies use internet services for both personal and business activities. The e-commerce business is Tokopedia. The reason of this take a look at is to decide and examine the influence of hedonic buying motivation, shopping way of life, positive emotion, and variety of selection on impulse searching for in Tokopedia online shop. The population in this study are consumers who use the Tokopedia application. The sample used turned into 100 respondents. The sampling technique is non opportunity sampling method. The method used is purposive sampling. The trying out tool used is SPSS. The test stages executed had been validity test, reliability test, normality take a look at, multicollinearity take a look at, heteroscedasticity take a look at, a couple of linear regression test, t test, F test, and coefficient of determination. The results of this study indicate that partially hedonic buying motivation, shopping way of life, positive emotion and variety of selection on impulse searching for in Tokopedia online shop. Simultaneously hedonic buying motivation, shopping way of life, positive emotion and variety of selection on impulse searching for in Tokopedia online shop.